Analyzing effects of sickle cell disease on morphometric and cranial growth in Indian population - Kumari Menka (Wolters Kluwer Medknow Publications, 2021)
Background: Sickle cell disease is the most pervasive autosomal recessive hereditary blood diseases and is characterized by the presence of sickle hemoglobin (HbS), which in turn gives rise to pathophysiological consequences. This HbS reduces the agility of erythrocytes plummeting their ability to pass through small vascular channels, which in turn results in increased blood viscosity and congestion of vascular beds, causing ischemia, local infarction, and hemolysis. Objectives: The current study was conducted to carry out the morphometric analysis in patients with sickle cell disease. Materials and Methods: This study was conducted on 75 subjects detected with sickle cell disease aged between 8 and 16.5 years. The study involved 38 males and 37 females. All the subjects were subjected to lateral cephalogram for the calculation of various angular and linear dimensions of the craniofacial structures. The linear measurements made were nasion-menton height, anterior nasal spine (ANS)-menton height, and nasion-ANS height, whereas the angular measurements made were Frankfurt mandibular plane angle, Frankfort mandibular incisor angle, and incisor mandibular plane angle. Results: Major chunk of the subjects had retruded mandible and vertical growth pattern. Few subjects exhibited with maxillary protrusion. Conclusion: It is concluded that early diagnosis and management of dental malocclusion in patients with sickle cell disease plays a pivotal role in an attempt to endow with a better quality of life to these individuals.